(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article presents the definition of a repetition as a stylistical device according to different sources of the field of stylistics. The main aim of this article to analyze and compare similarities and differences of repetition in both Uzbek and English languages. Showing as an example many works by different authors were searched and analyzed.